Silicon nitride ceramic composition, silicon nitride ceramic and preparation method thereof
By regulating the ratio of MgO, CaO and R2O3 in the silicon nitride ceramic composition, the growth of β-Si3N4 grains is promoted, and the problem of low strength of existing silicon nitride ceramic materials is solved, and high thermal conductivity and high strength performance are achieved Take into account both.
Patent Information
- Application Number
- CN202211176960.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-26
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-09-26
AI Technical Summary
The existing silicon nitride ceramic materials have low strength while improving thermal conductivity, making it difficult to take into account both high thermal conductivity and high strength performance.
By regulating the ratio of MgO, CaO and R2O3 in the silicon nitride ceramic composition, the viscosity of eutectics is reduced, the transformation of α-Si3N4 to β-Si3N4 grains is promoted, and the mass transfer rate of Si and N elements in the liquid phase is improved. , optimize the growth of β-Si3N4 grains and improve the thermal conductivity and strength of ceramics.
The high thermal conductivity and high strength properties of silicon nitride ceramics are achieved, and the density and performance stability of the ceramics are improved.
Smart Images

Figure CN117800740B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic materials, and in particular to a silicon nitride ceramic composition, a silicon nitride ceramic and a preparation method thereof. Background Art
[0002] Silicon nitride ceramics have high hardness, corrosion resistance, wear resistance, good high-temperature strength, and high thermal conductivity. It is an ideal thermal conductive material and has been widely used in metallurgy, aerospace, energy, machinery, military technology, optics, and glass industries.
[0003] β-phase silicon nitride is generally columnar, with grains with a large aspect ratio. The preferential growth of the c-axis is more obvious, and the thermal conductivity of the c-axis is higher. Therefore, the larger the aspect ratio of the grains, the higher the thermal conductivity. However, an excessively long aspect ratio will cause the density of the material to decrease, resulting in a decrease in thermal conductivity. In addition, the grain size in most silicon nitride ceramics currently presents a weak bimodal distribution. Coarse grains help to improve thermal conductivity, but correspondingly, the larger the grains, the lower the strength of the material. Therefore, it is necessary to develop silicon nitride ceramics that have both high thermal conductivity and high strength properties. Summary of the invention
[0004] The purpose of the present invention is to overcome the problems existing in the above-mentioned prior art and provide a silicon nitride ceramic having both high thermal conductivity and high strength.
[0005] The first aspect of the present invention is to provide a silicon nitride ceramic composition, which comprises 85-92% α-Si by mass. 3 N 4 Powder, 0-8% β-Si 3 N 4 Seed crystal, 0.1-3% MgO, 0.01-1% CaO, 3-8% R 2 O 3 , the total mass of MgO and CaO is recorded as m (Mg+Ca) , R 2 O 3 The mass is denoted as m R , m (Mg+Ca) and m R Satisfies the following relationship:
[0006]
[0007] Wherein, R is a rare earth element.
[0008] Preferably, the β-Si 3 N 4 The content of seed crystals is 2-8%.
[0009] Preferably, the β-Si3 N 4 The size of the seed crystal is 2-10 μm, and the aspect ratio is 1.5-3.
[0010] Preferably, the R 2 O 3 R in the above-mentioned embodiment includes at least one of cerium, praseodymium, neodymium, europium, gadolinium, erbium, thulium, ytterbium, lutetium and yttrium.
[0011] The second aspect of the present invention is to provide a silicon nitride ceramic, which is prepared by sintering the aforementioned silicon nitride ceramic composition.
[0012] Preferably, the silicon nitride ceramic comprises rod-shaped β-Si 3 N 4 The rod-shaped β-Si 3 N 4 In the grains, the length of β-Si is less than 2μm 3 N 4 The grain proportion is less than 30% and the length is 2-10μm. 3 N 4 The proportion of grains is 40-80%, and the length is greater than 10μm. 3 N 4 The proportion of grains is less than 30%.
[0013] Preferably, the rod-shaped β-Si 3 N 4 The average aspect ratio of the grains is 3-8.
[0014] The third aspect of the present invention is to provide a method for preparing silicon nitride ceramics, comprising the following steps:
[0015] S1: ball-milling the aforementioned silicon nitride ceramic composition, a solvent and a dispersant to obtain a slurry;
[0016] S2: mixing the slurry with a binder to obtain a spray slurry;
[0017] S3: spray drying the spray slurry and dry pressing to obtain a green body;
[0018] S4: sintering the green body in a nitrogen atmosphere to obtain silicon nitride ceramics.
[0019] Preferably, the sintering temperature is 1750-1900° C., and the sintering time is 2-10 h.
[0020] Preferably, the solvent includes at least one of ethanol, isopropanol, n-butanol, ethyl acetate, butyl acetate, butanone and cyclohexanone; the dispersant includes at least one of ammonium polyacrylate, triethyl phosphate, triolein, castor oil and triethanolamine; and the binder includes at least one of acrylic resin, polyvinyl alcohol and ethylene glycol.
[0021] The present invention adjusts the m in the silicon nitride ceramic composition. (Mg+Ca) and m R The ratio of MgO, CaO and R during sintering 2 O 3 The viscosity of the eutectic formed by the three decreases, promoting the 3 N 4 The transformation of the β-silicon nitride grains into β-silicon nitride grains and the increase of the mass transfer rate of Si and N elements in the liquid phase are beneficial to the uniform growth of β-silicon nitride grains, making the β-Si in the silicon nitride ceramics obtained after sintering 3 N 4 The grain concentration is good, silicon nitride ceramics have high strength and good thermal conductivity. DETAILED DESCRIPTION
[0022] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0023] The present invention provides a silicon nitride ceramic composition, which comprises 85-92% α-Si by mass percentage. 3 N 4 Powder, 0-8% β-Si 3 N 4 Seed crystal, 0.1-3% MgO, 0.01-1% CaO, 3-8% R 2 O 3 , the total mass of MgO and CaO is recorded as m (Mg+Ca) , R 2 O 3 The mass is denoted as m R , m (Mg+Ca) and m R Satisfies the following relationship:
[0024]
[0025] Wherein, R is a rare earth element.
[0026] In the present invention, when m (Mg+Ca) / mR When m is less than 0.5, the grains in the sintered ceramics show obvious bimodal distribution characteristics, the thermal conductivity is high, but the strength is significantly reduced; (Mg+Ca) / m R When it is greater than 1.2, the MgO, CaO and R 2 O 3 The viscosity of the liquid phase of the eutectic formed by the three is too low, and more liquid phase evaporates during sintering, resulting in insufficient density of the silicon nitride ceramic material, and a decrease in strength and thermal conductivity.
[0027] The present invention adjusts the m in the silicon nitride ceramic composition. (Mg+Ca) and m R The ratio of MgO, CaO and R during sintering 2 O 3 The viscosity of the eutectic formed by the three decreases, promoting the 3 N 4 To β-Si 3 N 4 The transformation of the grains and the increase of the mass transfer rate of Si and N elements in the liquid phase are beneficial to the uniform growth of β-silicon nitride grains, making the β-Si in the silicon nitride ceramics obtained after sintering 3 N 4 The grain concentration is good, silicon nitride ceramics have high strength and good thermal conductivity.
[0028] In some embodiments, β-Si is added to the silicon nitride ceramic composition. 3 N 4 Seed crystal, β-Si 3 N 4 The seed crystal will grow preferentially during sintering, increasing the β-Si 3 N 4 The average size of the grains increases the thermal conductivity of silicon nitride ceramics. 3 N 4 If the content of seed crystal is too high, the silicon nitride ceramic substrate obtained by sintering will be not dense enough and have poor strength. 3 N 4 The content of seed crystals is 2-8%.
[0029] In some embodiments, β-Si 3 N 4 The seed crystal size is 2-10 μm, and the aspect ratio is 1.5-3, which makes the sintered silicon nitride ceramics have good density. 3 N 4 If the aspect ratio of the seed crystal is too large, the silicon nitride ceramic will be easily broken during hot pressing and the densification will be affected. 3 N 4The seed crystal is too small, and the effect of preferential growth is not obvious; 3 N 4 If the seed crystal is too large, it is not conducive to the densification of silicon nitride ceramics.
[0030] In some embodiments, R 2 O 3 The R (rare earth element) in (rare earth element oxide) includes at least one of cerium, praseodymium, neodymium, europium, gadolinium, erbium, thulium, ytterbium, lutetium and yttrium. It can be better combined with MgO and CaO to form a sintering aid, thereby changing the growth of β-Si 3 N 4 The grain aspect ratio makes the β-Si in silicon nitride ceramics 3 N 4 The grains present a unimodal distribution (for example, the proportion of 2-10 μm grains is greater than the proportion of grains smaller than 2 μm and the proportion of grains larger than 10 μm), which improves the strength of silicon nitride ceramics; at the same time, the grain size is appropriately large to ensure the thermal conductivity of the ceramics.
[0031] In some embodiments, the silicon nitride ceramic composition may also contain a small amount of Al 2 O 3 , for example, less than or equal to 1wt%, to regulate the overall performance of the silicon nitride ceramic. If it is excessive, the thermal conductivity of the silicon nitride ceramic will be reduced.
[0032] The present invention also provides a silicon nitride ceramic, which is prepared by sintering the above silicon nitride ceramic composition.
[0033] In some embodiments, the silicon nitride ceramic comprises rod-shaped β-Si 3 N 4 The rod-shaped β-Si 3 N 4 In the grains, the length of β-Si is less than 2μm 3 N 4 The grain proportion is less than 30% and the length is 2-10μm. 3 N 4 The proportion of grains is 40-80%, and the length is greater than 10μm. 3 N 4 The proportion of grains is less than 30%. β-Si 3 N 4 The grain size concentration is good, β-Si 3 N 4 The average length of the grains is 3-10 μm, and the rod-shaped β-Si 3 N 4 The average aspect ratio of the grains is 3-8, which makes the silicon nitride ceramics have both high thermal conductivity and high strength properties.
[0034] In some embodiments, the four-point bending strength of the silicon nitride ceramic is 790-1000 MPa and the thermal conductivity is 60-82 W / (m*K).
[0035] The present invention also provides a method for preparing silicon nitride ceramics, comprising the following steps:
[0036] S1: ball-milling the aforementioned silicon nitride ceramic composition, a solvent and a dispersant to obtain a ball-milled slurry;
[0037] S2: mixing the ball milled slurry with a binder to obtain a spray slurry;
[0038] S3: spray drying the spray slurry and dry pressing to obtain a green body;
[0039] S4: sintering the green body in a nitrogen atmosphere to obtain silicon nitride ceramics.
[0040] In some embodiments, the aforementioned silicon nitride ceramic composition is mixed with a solvent and a dispersant and ball-milled for 12-30 hours, which is conducive to obtaining a uniformly mixed ceramic slurry. Optionally, the solvent includes at least one of ethanol, isopropanol, n-butanol, ethyl acetate, butyl acetate, butanone and cyclohexanone. The solvent can also be other organic substances with low boiling points. Optionally, the dispersant includes at least one of ammonium polyacrylate, triethyl phosphate, triolein, castor oil and triethanolamine. The dispersant can also be other agents with dispersing effects.
[0041] In some embodiments, the ball mill slurry is mixed with a binder and stirred for 4-8 hours to obtain a spray slurry. The addition of the binder can bind the various substances in the silicon nitride ceramic composition together, which is conducive to forming a spray slurry. Optionally, the binder includes at least one of acrylic resin, polyvinyl alcohol and ethylene glycol. The binder can also be other materials with bonding effects.
[0042] In some embodiments, spray drying is performed to obtain dry-pressed powder, and the spray drying temperature can be 180-260° C., and the moisture content of the dry-pressed powder can be reduced to below 0.8 wt %. The dry pressing pressure of dry pressing molding can be 180-220 MPa.
[0043] In some embodiments, the green body is sintered in a nitrogen atmosphere with a nitrogen pressure of 9.0-1.1 MPa, a sintering temperature of 1750-1900°C, and a sintering time of 2-10 hours, that is, when the temperature rises to 1750-1900°C, it is kept warm for 2-10 hours to promote the α-Si3N4 to fully undergo phase transformation into β-Si3N4 and grow into rod-shaped β-Si3N4 grains.
[0044] The present invention will be described in detail below by way of examples, but the present invention is not limited to the following examples.
[0045] Example 1
[0046] (1) 91.31wt% α-Si 3 N 4 , 2wt%β-Si 3 N 4 Seed crystal, 1.8wt%MgO, 0.89wt%CaO, 4wt%Y 2 O 3 Mix with ammonium polyacrylate and ethanol and ball-mill for 24 h to obtain ball-milled slurry;
[0047] (2) mixing the ball mill slurry with acrylic resin and stirring for 6 hours to obtain a spray slurry;
[0048] (3) spray drying the spray slurry to obtain silicon nitride dry pressed powder, the drying temperature being 220° C.;
[0049] (4) dry pressing the dry pressed powder to obtain a silicon nitride dry pressed body, with a dry pressing pressure of 200 MPa;
[0050] (5) The green body is placed in a nitrogen furnace for sintering, the nitrogen pressure is 1.0 MPa, the maximum temperature is 1800°C, and the holding time is 6 hours;
[0051] (6) After the sample is kept warm, it is cooled in the furnace and surface polished to obtain silicon nitride ceramics.
[0052] Example 2
[0053] (1) 91.2wt% α-Si 3 N 4 , 2wt%β-Si 3 N 4 Seed crystal, 2.3wt%MgO, 1.14wt%CaO, 3.36wt%Y 2 O 3 Mix with ammonium polyacrylate and ethanol and ball-mill for 24 h to obtain ball-milled slurry;
[0054] (2) mixing the ball mill slurry with acrylic resin and stirring for 6 hours to obtain a spray slurry;
[0055] (3) spray drying the spray slurry to obtain silicon nitride dry pressed powder, the drying temperature being 220° C.;
[0056] (4) dry pressing the dry pressed powder to obtain a silicon nitride dry pressed body, with a dry pressing pressure of 200 MPa;
[0057] (5) The green body is placed in a nitrogen furnace for sintering, the nitrogen pressure is 1.0 MPa, the maximum temperature is 1800°C, and the holding time is 6 hours;
[0058] (6) After the sample is kept warm, it is cooled in the furnace and surface polished to obtain silicon nitride ceramics.
[0059] Example 3
[0060] (1) 91.13wt% α-Si 3 N 4 , 2wt%β-Si 3 N 4 Seed crystal, 2.6wt%MgO, 1.29wt%CaO, 2.98wt%Y 2 O 3 Mix with ammonium polyacrylate and ethanol and ball-mill for 24 h to obtain ball-milled slurry;
[0061] (2) mixing the ball mill slurry with acrylic resin and stirring for 6 hours to obtain a spray slurry;
[0062] (3) spray drying the spray slurry to obtain silicon nitride dry pressed powder, the drying temperature being 220° C.;
[0063] (4) dry pressing the dry pressed powder to obtain a silicon nitride dry pressed body, with a dry pressing pressure of 200 MPa;
[0064] (5) The green body is placed in a nitrogen furnace for sintering, the nitrogen pressure is 1.0 MPa, the maximum temperature is 1800°C, and the holding time is 6 hours;
[0065] (6) After the sample is kept warm, it is cooled in the furnace and surface polished to obtain silicon nitride ceramics.
[0066] Example 4
[0067] (1) 89.31wt% α-Si 3 N 4 , 4wt%β-Si 3 N 4 Seed crystal, 1.8wt%MgO, 0.89wt%CaO, 3wt%Y 2 O 3 and 1wt%CeO 2 Mix with ammonium polyacrylate and ethanol and ball-mill for 24 h to obtain ball-milled slurry;
[0068] (2) mixing the ball mill slurry with acrylic resin and stirring for 6 hours to obtain a spray slurry;
[0069] (3) spray drying the spray slurry to obtain silicon nitride dry pressed powder, the drying temperature being 220° C.;
[0070] (4) dry pressing the dry pressed powder to obtain a silicon nitride dry pressed body, with a dry pressing pressure of 200 MPa;
[0071] (5) The green body is placed in a nitrogen furnace for sintering, the nitrogen pressure is 1.0 MPa, the maximum temperature is 1800°C, and the holding time is 6 hours;
[0072] (6) After the sample is kept warm, it is cooled in the furnace and surface polished to obtain silicon nitride ceramics.
[0073] Example 5
[0074] (1) 87.31wt% α-Si 3 N 4 , 6wt%β-Si 3 N 4 Seed crystal, 1.8wt%MgO, 0.89wt%CaO, 4wt%Y 2 O 3 Mix with ammonium polyacrylate and ethanol and ball-mill for 24 h to obtain ball-milled slurry;
[0075] (2) mixing the ball mill slurry with acrylic resin and stirring for 6 hours to obtain a spray slurry;
[0076] (3) spray drying the spray slurry to obtain silicon nitride dry pressed powder, the drying temperature being 220° C.;
[0077] (4) dry pressing the dry pressed powder to obtain a silicon nitride dry pressed body, with a dry pressing pressure of 200 MPa;
[0078] (5) The green body is placed in a nitrogen furnace for sintering, the nitrogen pressure is 1.0 MPa, the maximum temperature is 1800°C, and the holding time is 6 hours;
[0079] (6) After the sample is kept warm, it is cooled in the furnace and surface polished to obtain silicon nitride ceramics.
[0080] Comparative Example 1
[0081] (1) 91.54wt% α-Si 3 N 4 , 2wt%β-Si 3 N 4 Seed crystal, 1.5wt%MgO, 0.36wt%CaO, 4.6wt%Y 2 O 3 Mix with ammonium polyacrylate and ethanol and ball-mill for 24 h to obtain ball-milled slurry;
[0082] (2) mixing the ball mill slurry with acrylic resin and stirring for 6 hours to obtain a spray slurry;
[0083] (3) spray drying the spray slurry to obtain silicon nitride dry pressed powder, the drying temperature being 220° C.;
[0084] (4) dry pressing the dry pressed powder to obtain a silicon nitride dry pressed body, with a dry pressing pressure of 200 MPa;
[0085] (5) The green body is placed in a nitrogen furnace for sintering, the nitrogen pressure is 1.0 MPa, the maximum temperature is 1800°C, and the holding time is 6 hours;
[0086] (6) After the sample is kept warm, it is cooled in the furnace and surface polished to obtain silicon nitride ceramics.
[0087] Comparative Example 2
[0088] (1) 91.05wt% α-Si 3 N 4 , 2wt%β-Si 3 N 4 Seed crystal, 3.0wt%MgO, 0.83wt%CaO, 2.47wt%Y 2 O 3 Mix with ammonium polyacrylate and ethanol and ball-mill for 24 h to obtain ball-milled slurry;
[0089] (2) mixing the ball mill slurry with acrylic resin and stirring for 6 hours to obtain a spray slurry;
[0090] (3) spray drying the spray slurry to obtain silicon nitride dry pressed powder, the drying temperature being 220° C.;
[0091] (4) dry pressing the dry pressed powder to obtain a silicon nitride dry pressed body, with a dry pressing pressure of 200 MPa;
[0092] (5) The green body is placed in a nitrogen furnace for sintering, the nitrogen pressure is 1.0 MPa, the maximum temperature is 1800°C, and the holding time is 6 hours;
[0093] (6) After the sample is kept warm, it is cooled in the furnace and surface polished to obtain silicon nitride ceramics.
[0094] The performance tests of the silicon nitride ceramic samples of Examples 1-5 and Comparative Examples 1-2 are as follows:
[0095] Four-point bending strength: GBT 6569-2006 is used to test the four-point bending strength of silicon nitride ceramics.
[0096] Thermal conductivity: GB / T 39862-2021 is used to test the thermal conductivity of silicon nitride ceramics.
[0097] Grain size test: After polishing the silicon nitride ceramic sample, it was tested with an electron microscope, and the size of 100 grains was measured and counted.
[0098] Table 1
[0099]
[0100] It can be seen from the results in Table 1 that compared with Comparative Examples 1-2, the m (Mg+Ca) / m R The m of the sintered silicon nitride ceramic is less than 0.5, and the grains show obvious bimodal distribution characteristics (the proportion of grains less than 2 μm and the proportion of grains greater than 10 μm are both greater than the proportion of grains 2-10 μm), the thermal conductivity is high, but the strength is significantly reduced; the m of the comparative example 2 (Mg+Ca) / m R If the viscosity is greater than 1.2, the liquid phase viscosity is too low, and more liquid phase evaporates during sintering, resulting in insufficient density of silicon nitride ceramics, and both strength and thermal conductivity are reduced. However, the silicon nitride ceramics of the present application can simultaneously take into account high strength and high thermal conductivity.
[0101] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0102] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0103] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A silicon nitride ceramic composition, characterized in that: In terms of mass percentage, it includes 85-92% α-Si3N4 powder, 2-8% β-Si3N4 seed crystal, 0.1-3% MgO, 0.01-1% CaO, 3-8% R2O3, and the total mass of MgO and CaO is recorded as m (Mg+Ca) , the mass of R2O3 is recorded as m R , m (Mg+Ca) and m R Satisfies the following relationship: Wherein, R is a rare earth element.
2. The silicon nitride ceramic composition according to claim 1, characterized in that: The size of the β-Si3N4 seed crystal is 2-10 μm, and the aspect ratio is 1.5-3.
3. The silicon nitride ceramic composition according to claim 1, characterized in that: The R in the R2O3 includes at least one of cerium, praseodymium, neodymium, europium, gadolinium, erbium, thulium, ytterbium, lutetium and yttrium.
4. A silicon nitride ceramic, characterized in that: The silicon nitride ceramic composition is prepared by sintering the silicon nitride ceramic composition according to any one of claims 1 to 3.
5. The silicon nitride ceramic according to claim 4, characterized in that: The silicon nitride ceramic includes rod-shaped β-Si3N4 grains, among which the β-Si3N4 grains with a length less than 2 μm account for less than 30%, the β-Si3N4 grains with a length of 2-10 μm account for 40-80%, and the β-Si3N4 grains with a length greater than 10 μm account for less than 30%.
6. The silicon nitride ceramic according to claim 5, characterized in that: The average aspect ratio of the rod-shaped β-Si3N4 grains is 3-8.
7. A method for preparing silicon nitride ceramics, characterized in that: The following steps are involved: S1: ball-milling the silicon nitride ceramic composition according to any one of claims 1 to 3 with a solvent and a dispersant to obtain a slurry; S2: mixing the slurry with a binder to obtain a spray slurry; S3: spray drying the spray slurry and dry pressing to obtain a green body; S4: sintering the green body in a nitrogen atmosphere to obtain silicon nitride ceramics.
8. The preparation method according to claim 7, characterized in that: The sintering temperature is 1750-1900° C. and the sintering time is 2-10 hours.
9. The preparation method according to claim 7, characterized in that: The solvent comprises at least one of ethanol, isopropanol, n-butanol, ethyl acetate, butyl acetate, butanone and cyclohexanone; The dispersant comprises at least one of ammonium polyacrylate, triethyl phosphate, triolein, castor oil and triethanolamine; The binder includes at least one of acrylic resin, polyvinyl alcohol and ethylene glycol.
Citation Information
Patent Citations
Self-reinforced silicon nitride ceramic of high fracture toughness and method of preparing same
CN1048376A
Silicon nitride ceramic and preparation method thereof
CN105016738A